Effects of plant age on performance of the tropical perennial fodder grass, Cenchrus ciliaris L. subjected to elevated ultraviolet‐B radiation. (17th June 2020) - Hamid, A.; Singh, S.; Agrawal, M.; Agrawal, S. B.
Abstract: Abiotic stress, notably high ultraviolet‐B (eUV‐B), limit growth and productivity of many crop plants, but information on response of forage grasses to eUV‐B radiation is rather limited. The present study was therefore conducted to increase our understanding of differential age‐related responses on growth, metabolism and fodder quality of Cenchrus ciliaris ‐3108 (Buffel grass) to elevated UV‐B (eUV‐B: 7.2 kJ·m −2 ·day −1 ). Plant growth at both growth stages was notably reduced in response to eUV‐B, except for the number of nodes and tillers at vegetative and reproductive stages. At anthesis, tillering increased due to the perennial habit of this plant, but leaf senescence reduced the number of leaves per tiller. Unlike ambient UV‐B, eUV‐B at the vegetative stage resulted in diversion of photosynthate for the formation of secondary metabolites (tannins and phenolics), providing dual protection from photooxidative damage and from herbivory. The forage biomass as well as quality showed a marked decline under eUV‐B and relative nutritive value was reduced at both growth stages. Abstract : Growth wise differential responses of Cenchrus ciliaris L. to elevated UV‐B revealed dual protection against UV‐B and herbivory provided by metabolites at vegetative stage Twitter Handle: suruchi27.